2020
DOI: 10.3389/fendo.2020.568436
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Danshensu Inhibits Oral Cancer Cell Migration and Invasion by Modulating p38 Signaling Pathway

Abstract: Background: Oral squamous cell carcinoma (OSCC) that comprises about 90% of all oral cancer cases is associated with poor prognosis due to its highly metastatic nature. The majority of OSCC treatment options are related detrimental side-effects. Hypothesis/Purpose: The present study aimed at deciphering the effects of a bioactive phytochemical, sodium danshensu, on human oral cancer cell metastasis. Methods and Results: The treatment of FaDu and Ca9-22 cells with different doses of sodium danshensu (25, 50, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Salvianic acid A (Danshensu), a major water‐soluble component extracted from Salvia miltiorrhiza , is often converted into Sodium Danshensu to improve its chemical stability (Meng et al, 2019). A recent study showed that Sodium Danshensu inhibits oral cancer cell proliferation and metastasis (Kumar et al, 2020). However, as far as we know, whether Sodium Danshensu plays an anti‐cancer role in lung cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salvianic acid A (Danshensu), a major water‐soluble component extracted from Salvia miltiorrhiza , is often converted into Sodium Danshensu to improve its chemical stability (Meng et al, 2019). A recent study showed that Sodium Danshensu inhibits oral cancer cell proliferation and metastasis (Kumar et al, 2020). However, as far as we know, whether Sodium Danshensu plays an anti‐cancer role in lung cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Human normal bronchial epithelial cell (BEAS‐2B) and lung cancer lines (A549; NCI‐H1299) were obtained from ATCC (Manassas, VA, USA) and cultured in RPMI‐1640 medium (Gibco, CA, USA) supplemented with 10% FBS (Gibco, CA, USA), 1% streptomycin and penicillin in a humidified incubator with 5% CO 2 at 37°C. Then BEAS‐2B cells, A549 cells, and NCI‐H1299 cells were induced by various concentrations of Sodium Danshensu (25, 50, and 100 μM) for 24, 48, and 72 h (Kumar et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies deciphering the anti-metastatic effects of phytochemicals have shown sodium danshensu significantly inhibits the migration and invasion of human oral cancer cells by downregulating the phosphorylation of p38 [ 21 ]. Similarly, other bioactive plant compounds, such as Kahweol acetate and desacetylnimbinene, have been shown to inhibit cancer metastasis by reducing the phosphorylation of p38 [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] With regard to commonly used traditional Chinese medicine (TCM) herbal remedies, Danshen ( Radix Salviae Miltiorrhizae ) has reportedly demonstrated clear anti-inflammatory properties through tumor cell proliferation reduction via apoptotic cell activity and MAPK signaling decreases of oral cancer cells. [ 23 , 24 ] A meta-analysis conducted by Bae et al, [ 25 ] identified the herbal medicine exhibits the potential to increase natural killer cells in cancer patients. Furthermore, herbal medicine intervention demonstrates the potential to reduce multiple chemotherapy and radiotherapy induced side effects, such as xerostomia, gastrointestinal reactions, peripheral neuropathy, and pneumonitis.…”
Section: Introductionmentioning
confidence: 99%